Correction to: A general method for analyzing moderately large deflections of a non-uniform beam: an infinite Bernoulli–Euler–von Kármán beam on a nonlinear elastic foundation - Jang, T. S. (Acta mechanica, 2019)
We correct an error in the calculation of Eq. (30) of the original article as follows: